Nickel-catalyzed C(2)-H arylation of indoles with aryl chlorides under neat conditions - Pandey, Dilip K.; Vijaykumar, Muniyappa; Punji, Benudhar (Journal of Organic Chemistry, 2019)
Nickel-catalyzed regioselective C(2)-H arylation of indoles and pyrroles with aryl chlorides is achieved under neat conditions. This method allows the efficient coupling of diverse aryl chlorides employing a user-friendly and inexpensive Ni(OAc)(2)/dppf catalyst system at 80 degrees C. Numerous functionalities, such as halides, alkyl ether, fluoro-alkyl ether, and thioether, and substituted amines, including heteroarenes like benzothiazolyl, pyrrolyl, indolyl, and carbazolyl, are well tolerated under the reaction conditions. The preliminary mechanistic study highlights a single-electron transfer (SET) pathway for the arylation reaction.

Advances in transition-metal-catalyzed C-H bond oxygenation of amides - Vijaykumar, Muniyappa; Punji, Benudhar (Synthesis-Stuttgart, 2021)
C-O bond formation represents a fundamental chemical transformation in organic synthesis to develop valuably oxygenated (hetero)arenes. Particularly, the direct and regioselective C-H bond oxygenation of privileged amides, using a transition metal catalyst and a mild oxygenating source, is a step-economy and attractive approach. During the last decade, considerable progress has been realized in the direct C-H oxygenation of primary, secondary, and tertiary amides. This Short Review compiles the advances in transition-metal-catalyzed oxygenation of C(sp(2))-H and C(sp(3))-H bonds on various amides with diverse oxygenation sources. The review is categorized into two different major sections: (i) C(sp(2))-H oxygenation and (ii) C(sp(3))-H oxygenation. Each section is discussed based on the directing group (monodentate and bidentate) attached to the amide derivatives.
Keywords: Amides; C-H activation; directing group; Oxygenation; Transition Metal

Pd(II)-catalyzed chemoselective acetoxylation of C(sp(2))-H and C(sp(3))-H bonds in tertiary amides - Vijaykumar, Muniyappa; Punji, Benudhar (Journal of Organic Chemistry, 2021)
Palladium-catalyzed chemoselective C(sp(2))-H and C(sp(3))-H acetoxylation of synthetically useful tertiary amides is reported under relatively mild reaction conditions. This protocol proceeds through the assistance of a weakly coordinated directing group (C = O) and requires low catalyst (1.0 mol %) loading. Diverse functionalities, such as C(sp(2))-Cl, C(sp(3))-Cl, -CF3, -COOEt, and -NO2 groups, including morpholinyl, piperazinyl, and pyrrolidinyl heterocycles, are compatible under the reaction conditions. Further functionalization of this protocol is demonstrated by hydrolysis to alcohols, alcohol-acids, as well as reduction to tertiary amines. A preliminary kinetic isotope effect study supported the rate-limiting C-H bond activation process.

Palladium-catalyzed chemoselective oxygenation of C(sp2)-H and C(sp3)-H bonds in isatins - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Organic Letters, 2023)
The palladium-catalyzed chemoselective C(sp2)-H and C(sp3)-H bond oxygenation of substituted isatin derivatives is reported. This mild protocol exhibits the C5 C(sp2)-H oxygenation of isatins through electrophilic intermolecular C-H palladation in concentrated solutions using PhI(OAc)2 or Selectfluor as an oxidant, whereas it exhibits- N-CH3 C(sp3)-H oxygenation in dilute solutions via carbonyl-assisted intramolecular palladation in the presence of K2S2O8. This oxygenation reaction provides a direct and unified approach for synthesizing diverse oxygenated isatins with sensitive functionalities, including biorelevant compounds.

Chelation-assisted and steric-controlled selectivity in the Pd-catalyzed C-H/C-H oxidative coupling of indoles - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemical Communications, 2024)
We report the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst upon the strategic installation of N-pyridinyl and C3-carbonyl, which delivers 2,7-biindoles with a broad scope (25 examples; up to 93% yield). Isolation of the catalytic intermediate reveals the initial activation of the C(7)-H bond, followed by the C(2)-H bond in indoles, and the reaction proceeds via a Pd(ii)/Pd(0) pathway. This manuscript describes the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst through the strategic installation of N-pyridinyl and C3-carbonyl, which delivers diverse biorelevant 2-7-biindoles.

Palladium-catalyzed regioselective C(4)-H fluoroalkoxylation of indoles through weak chelation assistance - Vijaykumar, Muniyappa; Gonnade, Rajesh G.; Punji, Benudhar (ChemCatChem, 2025)
Installing fluoroalkyl motifs into biorelevant indoles is particularly interesting due to their ubiquitous presence in drug molecules. Herein, we demonstrate the regioselective C4 fluoroalkoxylation of indoles using fluoroalcohols via palladium-catalyzed chelation-assisted C & horbar;H activation. The weak chelating benzoyl moiety at the C3 position acts as a directing group for remote C(4)& horbar;H fluoroalkoxylation of diversely substituted indoles. This methodology demonstrates a high level of regioselectivity and tolerates a range of crucial functional groups, yielding diverse trifluoroalkoxylated indoles in moderate to good yields. Removal of directing/protecting groups and further functionalization established the synthetic utility of the methodology. A preliminary mechanistic investigation is conducted by isolating the palladacycle intermediate and performing the deuterium scrambling study. The regioselective C4 fluoroalkoxylation of indoles with various fluoroalcohols is achieved by the palladium-catalyzed weak chelation assistance strategy. The reaction is compatible for a range of important functionalities and proceeds via the intermediacy of a six-membered palladacycle following a Pd(II)/Pd(IV) pathway. image
Keywords: C-H activation; indoles; Palladium; Regioselective; Trifluoroalkoxylation